Novel and diary (Colloquia Comparativa Litterarum, 2025)
Taking as a starting point the ideas of such renowned researchers of autobiographical writing as Jean Rousset and Philippe Lejeune, this article examines the relations between the novel and the (personal) diary. Is their interaction mutually beneficial, or is it just the novel that takes advantage of it by borrowing certain elements from its less prestigious literary counterpart? To answer this question, the article first turns to Anne Frank’s diary, which is not a literary one in the strict sense of the word, and then goes on to analyse the use of diary writing in Daniel Defoe’s fiction (Robinson Crusoe and A Journal of the Plague Year), to finally consider two novels written entirely in the form of diaries, namely The Last Day of a Condemned Man by Victor Hugo and The Diary of a Country Priest by Georges Bernanos. One of the author’s conclusions is that the truly meaningful symbiosis between the novel and the diary can only take place once they have both acquired the status of autonomous genres and become partners engaged in a fruitful dialogue.
Keywords: novel and diary; living and writing; Anne Frank; Daniel Defoe; Georges Bernanos